2020
DOI: 10.1101/2020.04.21.20073759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic shift underlies recovery in reversible infantile respiratory chain deficiency

Abstract: Reversible infantile respiratory chain deficiency (RIRCD) is a rare mitochondrial myopathy leading to severe metabolic disturbances in infants, which recover spontaneously after 6 months of age. RIRCD is associated with the homoplasmic m.14674T>C mitochondrial DNA mutation, however only ∼1/100 carriers develop the disease. We studied 27 affected and 15 unaffected individuals from 19 families and found additional heterozygous mutations in nuclear genes interacting with mt-tRNAGlu including EARS2 and TRMU in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…Mitochondrial transcripts are among the most abundant mRNAs in axons [2,5,14,40,52,60], indicating their importance in local maintenance of axonal and synaptic mitochondria. We also observed a transcriptional upregulation of the serine and one carbon biosynthesis, an early-stage of integrated stress response, which may be caused by mitochondrial dysfunction [7,11,16]. These neuronal compensatory responses may be of relevance in patients who have the permanent impairment of GANP but have not been observed in studies of transient GANP depletion [1,58].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Mitochondrial transcripts are among the most abundant mRNAs in axons [2,5,14,40,52,60], indicating their importance in local maintenance of axonal and synaptic mitochondria. We also observed a transcriptional upregulation of the serine and one carbon biosynthesis, an early-stage of integrated stress response, which may be caused by mitochondrial dysfunction [7,11,16]. These neuronal compensatory responses may be of relevance in patients who have the permanent impairment of GANP but have not been observed in studies of transient GANP depletion [1,58].…”
Section: Discussionmentioning
confidence: 68%
“…Related to energy metabolic changes, CKB (brain-type creatine kinase) involved in compartmentalized ATP production and consumption was also upregulated [47]. Furthermore, upregulation of the serine and one-carbon biosynthesis pathway (PHGDH, PSAT1, SHMT2, MTHFD2) was detected, which is commonly observed in mitochondrial defects and as part of the integrated stress response [11,16].…”
Section: Ganp Regulates Gene Expression In Motor Neuronsmentioning
confidence: 99%
“…The rare nature of mtDNA-related disease will result in smaller cohorts than those typically utilised for common disorders, but genetic variation with large effect sizes should be identifiable, even in modestly sized studies, particularly if information from families is incorporated into the analyses [166]. Whole-genome sequencing and whole-exome sequencing are likely to be more effective than GWAS-based approaches if there is genetic heterogeneity, as is the case with secondary pathogenic nuclear variants necessary for the phenotypic expression of the homoplasmic m.14674T>C variant [159]. More recently, whole-genome sequencing and whole-exome sequencing have been applied to large population-based cohorts, such as the UK Biobank and Genomics England's 100 000 Genomes Project, enabling the identification of further carriers of mtDNA mutations within populations; these may be valuable resources that can be used for validation studies [101,102].…”
Section: Future Directionsmentioning
confidence: 99%
“…Very recently, digenic inheritance of mtDNA and nuclear variants has been demonstrated for reversible infantile respiratory chain deficiency, which is associated with the homoplasmic m.14674T>C mt-tRNA Glu variant, but shows reduced penetrance [158,159]. In affected patients, Hathazi et al discovered additional rare, heterozygous nuclear mutations in EARS2 and TRMU, which encode proteins responsible for aminoacylation of mt-tRNA Glu and mt-tRNA Gln and cysteine-dependent thiouridylation of mt-tRNA Glu , as well as other genes involved in glutamate or glutamine metabolism.…”
Section: Mito-nuclear Crosstalkmentioning
confidence: 99%
“…WES in healthy and affected m.14674T>C carriers found that the majority of affected individuals also harboured heterozygous variants in nuclear genes known to interact with mt-tRNA Glu . For example, some individuals carried deleterious mutations in EARS2, which encodes a protein that aminoacylates the 3' end of the tRNA molecule 76 .…”
Section: [H3] Digenic-digenomic Inheritancementioning
confidence: 99%